A educação ambiental chega de barco na vila de pescadores da Barra do Superagui - Farias, Ariadne Sílvia de (2009)
This dissertation consists in a case study that aims to make a diagnosis of practices that include the Environmental Education (EE) in Barra do Superagui. In order to get elements to discuss the process of EE in Conservation Units (CU), it is considered the peculiar social dynamic of the fishermen village as a way to assess the needs and educational proposals adopted at the local community in the context of social valorization and the historical, cultural and natural conservation of the Superagui National Park. Thus, the research is proposed based on the case study as a methodological procedure, whereas the observation is the main resource of investigation. It supported this methodological procedure in order to examine how the EE activities reflect and/or transform the relationship between individuals of the Barra do Superagui community. The results obtained from this study stand out through the reports of the island residents, during the conversations and interviews made in the field. They revealed the lack of efficiency of environmental management of the CU in question as well as the EE activities proposed by Non Governmental Organizations (NGOs) to the local community. From the observations of some practices that occurred during the field work, and according to reports from residents, they revealed that in most cases the institutions which promote the EE in Barra do Superagui do not know the local socialenvironmental reality and/or do not consider the peculiar sociocultural aspects of the traditional caiçara culture. Therefore, it is necessary to rethink the educational proposals implemented by both the NGOs and the national manager of UC. Accordingly, it is believed that the principles and concepts postulated by EE emancipation are efficient and should be given credit to the educational programs that seek for improvement in the life quality of the traditional populations inserted in CU, such as the caiçaras of Barra do Superagui.